Cohort study of osteoporosis and fracture risk in Wales: does secondary prevention achieve any benefit?. (2018) - North, Laura; Davies, Llion; Berridge, Damon; Walters, Angharad; Akbari, Ashley; Lyons, Ronan
No abstract available